2017
DOI: 10.1177/1591019917721867
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of arteriovenous malformation hemodynamic changes after endovascular treatment using parametric color coding: A case series study

Abstract: Background Brain arteriovenous malformations (AVMs) are complex vascular lesions. Endovascular treatment results are usually measured by calculating the volume reduction of the lesions. Nevertheless, vascular flow quantification seems a more physiologically accurate way of measuring endovascular results. We evaluated the use of parametric color coding (PCC) with digital subtraction angiography (DSA), in order to determine the feasibility of PCC to detect and measure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Patients were divided into 3 groups following the distribution of angiographic peculiarities and adapting recently suggested thresholds to quantify interventional AVM embolization volumes ( Table 1 and Fig 1). 11 In case of an overlap of different perfusion patterns or distinct feeding varieties in 1 individual, the following grade was applied. Furthermore, flow rates for both the ICA and ECA supply were classified as suggested by Koo et al 5 The flow rate was classified as high if the draining vein was seen at the same time or 1 frame after visualization of the nidus.…”
Section: Radiologic Evaluationmentioning
confidence: 99%
“…Patients were divided into 3 groups following the distribution of angiographic peculiarities and adapting recently suggested thresholds to quantify interventional AVM embolization volumes ( Table 1 and Fig 1). 11 In case of an overlap of different perfusion patterns or distinct feeding varieties in 1 individual, the following grade was applied. Furthermore, flow rates for both the ICA and ECA supply were classified as suggested by Koo et al 5 The flow rate was classified as high if the draining vein was seen at the same time or 1 frame after visualization of the nidus.…”
Section: Radiologic Evaluationmentioning
confidence: 99%
“…To date, color-coded quantitative DSA, rather than quantitative fluoroscopy, has been the subject of all clinical investigations resulting from these technical advances. ese studies have investigated a variety of functional parameters, with the aim of extracting objective hemodynamic data from DSA imaging during peripheral arterial and cerebrovascular interventions [6,9,12,[15][16][17][18][19]. Kostrzewa et al investigated FWHM and TTP as parameters for treatment evaluation of SFA and AP lesions, demonstrating that both parameters could be used to assess treatment success independent of ABI value [6].…”
Section: Discussionmentioning
confidence: 99%
“…109,110 These studies are promising, and more recent work has expanded the technology to 3D datasets 111 and treatment assesments. 73 More work needs to be done validating the parametric color-coding method in addition to bAVM hemodynamics and natural history in general.…”
Section: Methods For Flow Assessmentmentioning
confidence: 99%
“…There is evidence of agreement between the modalities on this measure; for example, Brunozzi et al and Shakur et al reported correlation between MR‐based flow analysis and DSA‐based contrast time‐density curves, with the former also noting that ICH presentation was more common in those with decreased venous transit times and the latter decreased MTT and seizure presentation . These studies are promising, and more recent work has expanded the technology to 3D datasets and treatment assesments . More work needs to be done validating the parametric color‐coding method in addition to bAVM hemodynamics and natural history in general.…”
Section: Alteration Of Hemodynamics Exacerbates Bavm Hemorrhagementioning
confidence: 98%
See 1 more Smart Citation